The computational thermodynamic modelling of the phase equilibria pertaining to the IiO₂ - Ti₂O₃ - FeO slag system - Fourie, David Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2004.